Kinematics and shock attenuation during a prolonged run on the athletic track as measured with Inertial Magnetic Measurement Units - Reenalda, J.; Maartens, E.; Buurke, J. H.; Gruber, A. H. (Gait and Posture, 2018)
Background: Tibial stress fractures are common running related injury and their etiology may include biomechanical factors like impact forces, shock attenuation, lower limb kinematics and how these factors are influenced by intense or prolonged running. Inertial-magnetic measurement units (IMUs) have recently emerged as an alternative to motion capture but their use to date was mostly limited to segmental and joint motion.